STRATEGI PEMBELAJARAN METODE EKSPLORASI UNTUK PEMBELAJARAN TEKS PROSEDUR SISWA KELAS VII MTsN 2 PADANG - Mardhiyyah, Zulfa Salsabila; Azzahra Qalbi Firma, Fadia; Navaro, Zaki; Navita, Muthia; Zalianti Fitri, Tiffani; Olva Zuve, Farel (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the exploration method as a learning strategy to develop the creativity of seventh-grade students at MTsN 2 Padang in learning procedural texts. The research employed a qualitative approach using a Classroom Action Research design conducted in two cycles. Data were collected through classroom observations, teacher interviews, and analysis of students’ work. The findings indicate that the exploration method significantly improves students’ activeness, confidence in expressing ideas, and the quality of their work. Students became more independent in generating ideas and showed notable development in creativity aspects, including originality, flexibility, and elaboration of ideas. The majority of students achieved high creativity scores, ranging from 92 to 100. These results confirm that the exploration method is an effective learning strategy in promoting meaningful learning experiences and fostering students’ creativity in Indonesian language instruction.